Energy, exergy and efficiency analysis of a flat plate solar collector used as air heater - Muhammad Hanif,; Mansoor Khan, Khattak; Maazullah Khan,; Muhammad Ramzan,; Abdurab, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Air heating by solar collectors is renewable technology providing hot air for different purposes. The present research emphasizes on analysis of energy, exergy and efficiency of a flat plate solar air heater. The analysis model was tested on five different air mass flow rates of 0.5 (Natural), 1.31, 2.11, 2.72 and 3.03 kgs-1 under three different tilt angles of 25, 35 (Recommended) and 50o. The data was replicated three times making a total of 45 treatments. A two factorial completely randomized design was used to find if there is any significant difference among the treatments. The results showed that the solar collector gave better performance at air mass flow of 3.03 kgs-1 under tilt of 35o. At maximum air mass flow rate of 3.03 kgs-1and optimum tilt angle of 35o the maximum energetic efficiency of 51%, while minimum exergetic efficiency of 24% and maximum overall efficiency of 71% were recorded. It was concluded that to get maximum thermal efficiencies of 71% from flat plate solar collector used as an air heater must be operated at high air mass flow rates of 3.03 kgs-1under 35o tilt angle at Peshawar, Pakistan.